2015
DOI: 10.1080/00268976.2015.1025112
|View full text |Cite
|
Sign up to set email alerts
|

A corresponding-states framework for the description of the Mie family of intermolecular potentials

Abstract: The Mie (λ r , λ a) intermolecular pair potential has been suggested as an alternative to the traditional Lennard-Jones (12-6) potential for modelling real systems both via simulation and theory as its implementation leads to an accuracy and flexibility in the determination of thermophysical properties that cannot be obtained when potentials of fixed range are considered. An additional advantage of using variable-range potentials is noted in the development of coarse-grained models where, as the superatoms bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 69 publications
3
71
0
Order By: Relevance
“…The repulsive exponent n varies between 24 and 39, which compares favorably with Avendaño et al [7], who used a repulsive exponent of n = 23, but a different dispersive exponent, and Maurer [85], who used exponents of n = 30 and n = 33 for a perturbation theory. Ramrattan et al concluded that a repulsive exponent n = 31 should be used for an attractive exponent of m = 6 [23]. Comparing the Pareto set of the Mie and the 2CLJQ model shows that the latter enables a better description of the studied data of CO 2 .…”
Section: Systematic Study Of the Vapor-liquid Equilibriummentioning
confidence: 99%
“…The repulsive exponent n varies between 24 and 39, which compares favorably with Avendaño et al [7], who used a repulsive exponent of n = 23, but a different dispersive exponent, and Maurer [85], who used exponents of n = 30 and n = 33 for a perturbation theory. Ramrattan et al concluded that a repulsive exponent n = 31 should be used for an attractive exponent of m = 6 [23]. Comparing the Pareto set of the Mie and the 2CLJQ model shows that the latter enables a better description of the studied data of CO 2 .…”
Section: Systematic Study Of the Vapor-liquid Equilibriummentioning
confidence: 99%
“…Our adoption of the particular Mie (λ,6) form in preference to the general form where both exponents are left as adjustable parameters follows from the observation that, for the description of fluid phase behaviour, the repulsive and attractive exponents are correlated [16]; this correlation reduces the degrees of freedom, thereby allowing the attractive exponent to be fixed to the London-dispersion value of six.…”
Section: Generalitiesmentioning
confidence: 99%
“…The first or traditional way is to force the EoS to fit the available fluid phase equilibrium data (experimental measurements or molecular simulation data), (i.e., vapor pressure and liquid density data), and second derivative properties. 40 A second option is using the corresponding states principle, 41,42 in terms of conformational parameters of the Mie potential. In the latter case, as it was recently demonstrated, once m s and a are fixed, the remaining parameters can be calculated using the acentric factor (which defines the r value), critical temperature (which defines the " value), and the liquid density evaluated at 0.7 of the critical temperature (which defines the value).…”
Section: A Saft-coarse Grained Mie Force Fieldmentioning
confidence: 99%